Penanda Fatis dalam Bahasa Jawa yang Digunakan oleh Masyarakat Madura di Jember - Siti Yuliana (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2017)
Abstract This article discusses is phatic marker in Javaneese language (BJ) that is used by Madureese society in Jember. Madura speaker when talking on BJ, then the marker is a marker spoken phatic is phatic BM. In terms of speakers, in the form of BJ phatic marker used by the Madurese community in Jember assortment as well as in terms of the use and distribution also varies. There are three steps that are used in this research, which are 1) data collection steps, 2) data analysis step, 3) presentation of the data analysis. Result step the method that is used in the data collection step is simak method. The second step is data analysis step, which are agih method. The third step is the presentation of the data analysis result is informal method. Based on research results, he form of phatic communion in BJDJ are in the form of 1) particles 2) phatic words, 3) word repetitions, and 4) the use of affixes. Phatic communion is particles, which are jhâ’, kan, ko dan ra, yâ, lâ, pas, ta, dhing, ki, lah, and mbok. Phatic communion is phatic words, which are sènga’, ma’, adâ’, bâh, mara, jeneng, mboh, wés, and mayo’. Phatic communion is word repetitions,which are cén, ndak, jal, mboh, yo, and iku. Phatic communion is use of affixes, which are –an and –en. Key words: Phatic marker, particles, phatic words, word repetitions, the use of affixes